The Role of Information Systems in Control Raw Material Supply Using The Exponential Smoothing Method: Case Study at PT Sugar Group Companies - Rahman, Fatmawati A; Masmarulan; Rostini; Muhammad, A Fadel; Bakri, Risna melati sukma (Economics and Business Journal (ECBIS), 2024)
PT Sugar Group Companies requires an information system that affects raw material inventory control. In this research, the Exponential Smoothing method is implemented to estimate the amount of raw materials needed in the future. This method is useful for companies to carefully calculate the amount of raw materials needed, this can reduce the budget and increase operational capabilities. The results of the study state that the Exponential Smoothing method can be used effectively in raw material inventory control information systems, both in industries that have high differences in demand for raw materials. Therefore, this system can facilitate PT Sugar Group Companies in optimizing the use of resources and developing service quality.